Weaving the Memory of the Other: The Conquest of Oran’s Cartoons, in 1732, and the (Anti)Islamic Imagery in the Context of the Spanish Campaigns in Algeria - Rega Castro, Iván (Eikón / Imago, 2020)
The reconquest of Oran by Spanish Army, ordered by Philip V in 1732, was essential in the articulation of its image of power. The aim of this research is to reconstruct, with a diachronic approach, the (anti)Islamic imagery of the Spanish campaigns in Algeriaduring the Early Modern period, and the making of the new The conquest of Oran’s image.